2018
DOI: 10.1542/hpeds.2017-0211
|View full text |Cite
|
Sign up to set email alerts
|

A Hospital-Based Initiative to Reduce Postdischarge Sudden Unexpected Infant Deaths

Abstract: A comprehensive sleep safety culture change can be effectively integrated into a nursery setting over time by using feedback from Child Fatality Review and performance improvement methodology. Repeated messaging and education by the entire nursery staff has the potential to play a role in reducing sleep-related deaths in infants born at their hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Historically, SUID and safe sleep educational efforts were focused on the NICU and newborn nursery encounters ( 7 ). Our results suggest a need to re-balance these efforts to include outpatient primary care practices (the most frequent presentation in our cohort) and inpatient hospitalizations (where length of stay provides multiple opportunities for education and modeling).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, SUID and safe sleep educational efforts were focused on the NICU and newborn nursery encounters ( 7 ). Our results suggest a need to re-balance these efforts to include outpatient primary care practices (the most frequent presentation in our cohort) and inpatient hospitalizations (where length of stay provides multiple opportunities for education and modeling).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals are uniquely positioned to educate new parents about infant safe sleep at every encounter. Safe sleep initiatives have historically targeted nursery care and neonatal intensive care unit (NICU) hospitalizations, with nursery-based safe sleep programs successfully resulting in reduced average SUID rates post-intervention ( 7 ). Studies addressing safe sleep during outpatient primary care physician visits, inpatient general pediatric admissions, and emergency room visits are limited, however promising new data shows that parent knowledge and practice of infant safe sleep are influenced by in-hospital interventions, with parents more likely to place their infants in a supine position and use a crib following intensive hospital educational efforts ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms that account for some of the variables discussed in this report have been developed on the basis of literature review, expert opinions, and unit consensus. 14,251 254 The authors concluded that repeated messaging and education by the entire nursery staff has the potential to play a role in reducing sleep-related deaths in infants born at a hospital.…”
Section: Human Milk and Breastfeedingmentioning
confidence: 99%
“… 11 , 12 Nursery-based safe sleep programs have reduced average SUID death rates postintervention. 13 However, recent research suggests that infants are not placed in safe sleep environments when admitted to a hospital, resulting in a new focus on targeting safe sleep within hospital policies. 14 , 15 The objectives of this study were to analyze the sleep practices of hospitalized infants, assess adherence to the AAP safe sleep guidelines, and develop interventions to improve adherence to these guidelines at our hospital.…”
Section: Introductionmentioning
confidence: 99%